Bacteria Associated With Shiraia Fruiting Bodies Influence Fungal Production of Hypocrellin A - Ma, Yan Jun; Zheng, Li Ping; Wang, Jian Wen (Frontiers in Microbiology, 2019)
Hypocrellin A (HA) is a natural red perylenequinone pigment from Shiraia fruiting body, which was used clinically on various skin diseases and developed as a photodynamic therapy (PDT) agent against cancers. The fruiting bodies may harbor a diverse but poorly understood microbial community. In this study, we characterized the bacterial community of Shiraia fruiting body using a combination of culture-based method and Illumina high-throughput sequencing, and tested the involvement of some companion bacteria in fungal HA production by the fungal-bacterial confrontation assay. Our results revealed that the bacterial community in the fruiting body was dominated by Bacillus and Pseudomonas. Some Pseudomonas isolates such as P. fulva, P. putida, and P. parafulva could stimulate fungal HA accumulation by Shiraia sp. S9. The bacterial treatment of P. fulva SB1 up-regulated the expression of polyketide synthase (PKS) for HA biosynthesis and transporter genes including ATP-binding cassette (ABC) and major facilitator superfamily transporter (MFS) for HA exudation. After the addition of live P. fulva SB1, the mycelium cultures of Shiraia sp. S9 presented a higher HA production (225.34 mg/L), about 3.25-fold over the mono-culture. On the other hand, B. cereus was capable to alleviate fungal self-toxicity from HA via down-regulation of HA biosynthetic genes or possible biodegradation on HA. To our knowledge, this is the first report on the diversified species of bacteria associated with Shiraia fruiting bodies and the regulation roles of the companion bacteria on fungal HA biosynthesis. Furthermore, the bacterial co-culture provided a good strategy for the enhanced HA production by Shiraia.